Overview of UV Light Exposure on Airborne Bacterial Growth in the Transmitted Transfusion Infections and Donor Selection Laboratory - Gravinda Widyaswara; Kumara Rahmawati Zain (Indonesian Journal of Biology Education, 2026)
Air sterilization is an essential effort to maintain air quality in educational laboratory settings. Ultraviolet (UV) light, particularly UV-C, is known to be effective at reducing of airborne microorganisms. This study aimed to describe the effect of UV light exposure on airborne bacterial growth in the Transfusion Transmitted Infections (TTI) Laboratory and the donor selection at Guna Bangsa College of Health Sciences, Yogyakarta. This research employed a descriptive observational method with a cross-sectional design. Air sampling was conducted after UV exposure using the settle plate method on Nutrient Agar (NA) media for 30 minutes, placed at several points within the laboratory, and incubated at 37°C for 24 hours. The results showed that the TTI’s Laboratory had 3 CFU/m³ and the Donor Screening Room had 2 CFU/m3. These results remain well below the maximum allowable airborne bacterial colony count set by the Indonesian Ministry of Health Regulation No. 70 of 2016, which limits it to at 500 CFU/m³. This indicates that the air quality in both laboratories meets the microbiological cleanliness standard, although the UV disinfection was not fully effective.